Introvert Character In The Novel Titled Sin By Faradita (Carl Gustav Jung Theory) - Ilham Ridhoyansyah Putra; Suyatno Suyatno (PIKTORIAL : Journal of Humanities, 2021)
This study aims to (1) describe the introverted personality of Raga Angkasa in the novel Sin by Faradita, (2) describe the factors that cause the introverted personality of Raga Angkasa in the novel Sin by Faradita. This study used descriptive qualitative method. The object studied in this study is the novel Sin. Data was obtained by collecting data with basic techniques, namely reading the whole novel and then determining written data, transferring it into notes, collecting library data sources and data from other sources, and reading library data sources. The theoretical reference used regarding introverted personality is Carl Gustav Jung's theory. The result of this research can be concluded that the personality of Raga Angkasa character includes thinker type, feeling type, sensation type and intuitive type. While the factors that cause introverted personality include: Activity, Socialiability, Risk Talking, Impulsiveness, Expressiveness, Reflectiveness, and Responsibility.Keywords: Introvert, Novel, Personality, Character.